(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the main problems faced by teenagers, their causes, and possible solutions. Teenagers go through various psychological, physical, and social challenges. The article also highlights the role of parents, teachers, and society in addressing these issues. Moreover, it analyzes ways to communicate effectively with teenagers and support them during this crucial stage.